Determining skyrmion stability from its nucleation and annihilation rates - Foo, Yi Ling (Nanyang Technological University, 2020)
Magnetic skyrmions are nanoscale magnetization textures that are found in magnetic materials. In general, magnetic skyrmions are topologically protected and are relatively stable due to their topological nature. Skyrmions are quasiparticles that can be moved, nucleated and annihilated and can potentially be exploited for data storage and logic devices. Thus, a characterization method for the skyrmion stability and data retention is required for the realization of skyrmionics devices. In this project, the time-dependent magnetization of skyrmion-stable magnetic thin films under varying magnetic fields is measured by using a Kerr microscope. A theoretical model for the skyrmion nucleation and annihilation rates of skyrmions is developed to extract the energy barrier height and lifetime of skyrmions. The method developed in this thesis provides a convenient method for the characterization of skyrmion stability.